Do investors react differently on friday’s earnings announcements? - Nurwati Ashikkin Ahmad Zaluki; Ahmad Ridhuwan Abdullah; Salwani Abdullah; Zarina Alassan (2012)
this paper examines whether markets react differently to earnings announcements released on Fridays versus non-Fridays in the Malaysian capital market. we use a standard event study method using a market-adjusted return model to examine such differences based on a sample of 120 earnings announcements. the results show that announcements of profits released by companies on Fridays have a negative effect on stock prices while announcements of losses are associated with positive effects. these results contrast with the results observed when the earnings announcements are released on nonFriday, thus confirming that such differences exist in the Malaysian capital market.